Antimycobacterial and antifungal isosters of salicylamides - Waisser, Karel; Pesina, Milan; Holý, Pavel; Pour, Milan; Bures, Otakar; Kunes, Jisí; Klimesová, Vsra; Buchta, Vladimír; Kubanová, Petra; Kaustová, Jarmila (Archiv der Pharmazie, 2003)
A set of 40 derivatives of 3-hydroxypicolinic acid and 2-sulfanylbenzoic acid, isosteric to salicylanilides was synthesized. The compounds were evaluated for in vitro activity against Mycobacterium tuberculosis, Mycobacterium kansasii and Mycobacterium avium, Candida albicans, Candida tropicalis, Candida krusei, Candida glabrata, Trichosporon beigelii, Aspergillus fumigatus, Absidia corymbifera, Trichophyton mentagrophytes and Microsporum gypseum. Structure-activity relationships of antimycobacterial activity and antifungal activity against T. mentagrophytes and M. gypseum were analyzed by the Free-Wilson method. An increase in antimycobacterial activity was observed only for the sulfanylbenzoic acid derivatives, especially those with the benzyl moiety. The antifungal activity was not significant.
Keywords: kyseliny pikolinové; Sulfanilic Acids; salicylany; Antifungal Agents; mikrobiální testy citlivosti; Structure-Activity Relationship; antiinfekční látky; sulfhydrylové sloučeniny; Anti-Infective Agents; Anti-Bacterial Agents; Picolinic Acids; salicylanilidy; Microbial Sensitivity Tests; Benzoic Acid; benzoáty; racionální návrh léčiv; Benzoates; Sulfhydryl Compounds; Drug Design; vztahy mezi strukturou a aktivitou; kyselina benzoová; Salicylates; antibakteriální látky; antifungální látky; Salicylanilides; kyseliny sulfanilové